High volume liposuction in tumescence anesthesia in lipedema patients: a retrospective analysis - Sandhofer, Matthias; Hofer, Victoria; Sandhofer, Martina; Mindt, Sonani; Moosbauer, Werner; Barsch, Martin (Journal of drugs in dermatology, 2021)
Background: Lipedema is a chronic, progressive disease that occurs almost exclusively in women and leads to pathological, painful fat growths at the extremities. Only symptomatic therapy can be offered since the etiology of the disease has not yet been clarified. Liposuction in tumescent anesthesia has established itself as a surgical treatment method of choice. The complication rate associated with the procedure and the pharmacological course and safety of treatment in patients with lipedema has not yet been sufficiently studied. The aim of the study was to broaden the evidence on the safety of ambulatory high-volume liposuction in tumescent anesthesia in lipedema patients. Influencing factors of patients (weight, fat content, comorbidities) or the process technique (drug administration, volume of aspirates) should be investigated on the safety and risks of tumescent anesthesia. This was a retrospective data analysis in which data from 27 patients (40 liposuction procedures) treated at the Sandhofer and Barsch lipedema center between 2016 and 2018 were evaluated. The liposuctions were carried out in tumescent anesthesia and using a Power-Assisted Liposuction system. Clinical examinations and regular blood samples were carried out before the procedure, intra- and postoperatively. The procedures lasted an average of 118 minutes and an average of 6111 ml of aspirate was removed. For tumescent anesthesia, patients were given an average lidocaine dose of 34.23 mg/kg body weight and an epinephrine dose of 0.11 mg/kg body weight. No relevant complications associated with drug side effects, hypovolemia or hypervolemia or blood loss were detected. Liposuction under high volume tumescent anesthesia for the treatment of lipedema patients is, even for major intervention, a safe procedure. J Drugs Dermatol. 20(3):326-334. doi:10.36849/JDD.2021.5828High Volume Liposuction, Tumescence Anesthesia, Lipedema
Gesehen am 23.07.2021